The Influence of Emotional Intelligence on Social Science Learning Achievement Class VIII Students at SMP Negeri 1 Sungai Ambawang - Gloria Kristia Pagari; Aminuyati Aminuyati; Venny Karolina; Hadi Wiyono; Yusawinur Barella (Universitas Muhammadiyah Enrekang, 2023)
There is a perspective if intellectual intelligence is the only factor in achieve learning achievement so that efforts to develop emotional intelligence do not noticed. This study aims to determine the effect of emotional intelligence on social science learning achievement in class VIII students at SMP Negeri 1 Sungai Ambawang. This research using quantitative methods with a population of 112 from class VIII at SMP Negeri 1 Sungai Ambawang. Sampling using the simple random sampling technique, so obtained a sample of 88. Data collection using a questionnaire and social science value data as research instrument, then to look for the effect of emotional intelligence on achievement study social science using a simple linear regression test using SPSS 24. From the results of data collection known if there are 47 samples that have high emotional intelligence and 41 with a level moderate, then from the Social science final exam scores there were 76 samples who passed and 12 people did not complete. It was found that the R square value was 0.616, this result is significant if emotional intelligence affect social science learning achievement by 61.6%. From the value of R square it can be concluded if intelligence emotional has an influence on social science learning achievement in class VIII students at SMP Negeri 1 Sungai Ambawang.